2006
DOI: 10.1038/sj.gt.3302864
|View full text |Cite|
|
Sign up to set email alerts
|

Immunization against MUC18/MCAM, a novel antigen that drives melanoma invasion and metastasis

Abstract: Melanoma patients with metastases have a very low survival rate and limited treatment options. Therefore, the targeting of melanoma cells when they begin to invade and metastasize would be beneficial. An adhesion molecule that is upregulated at the vertical growth phase is the melanoma cell adhesion molecule (MCAM/MUC18). MUC18 is expressed in late primary and metastatic melanoma with little or no expression on normal melanocytes. We utilized the alphavirus-based DNA plasmid, SINCp, encoding murine MUC18 (SINC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 28 publications
(22 reference statements)
0
36
0
Order By: Relevance
“…51 Although an earlier study found no direct correlation between its expression and metastatic behavior of melanoma, 52 an increasing body of work has shed light on the functions of MCAM, particularly about its role in tumor growth and the progression of human malignant melanoma. 51,[53][54][55] Our MS-based quantitative proteomic data and immunostaining results (Figure 5B) consistently demonstrated the overexpression of MCAM in the metastatic over the primary melanoma cells. These results support that MCAM may serve as a diagnostic marker for monitoring the progression of melanoma.…”
Section: Characterization Of the Differential Expression Of Cell Surfmentioning
confidence: 99%
“…51 Although an earlier study found no direct correlation between its expression and metastatic behavior of melanoma, 52 an increasing body of work has shed light on the functions of MCAM, particularly about its role in tumor growth and the progression of human malignant melanoma. 51,[53][54][55] Our MS-based quantitative proteomic data and immunostaining results (Figure 5B) consistently demonstrated the overexpression of MCAM in the metastatic over the primary melanoma cells. These results support that MCAM may serve as a diagnostic marker for monitoring the progression of melanoma.…”
Section: Characterization Of the Differential Expression Of Cell Surfmentioning
confidence: 99%
“…An estimated 62,480 new cases of melanoma were diagnosed in the United States during 2008, 8,420 of which resulted in death (2). The transition of melanoma from the radial growth phase to the vertical growth phase to metastasis is accompanied by multiple molecular changes (3)(4)(5)(6)(7)(8). We and others have shown that two transcription factors, activating transcription factor-1 (ATF-1) 2 and cAMP-response element-binding protein (CREB), are activated and overexpressed in melanoma during its progression toward the malignant phenotype (9 -13).…”
mentioning
confidence: 99%
“…Previously, targeting CD146 with antibody against the molecule has been shown to inhibit tumor growth and angiogenesis in several types of cancer. Based on these findings (16,22,23), we chose to explore whether the induced expression of CD146 protected tumor cells from HDACiinduced death. We further tested whether the antitumoral activity of HDACi could be significantly enhanced in combination with the targeting of CD146.…”
mentioning
confidence: 99%